Mewujudkan SDM Unggul di Bidang Perdagangan melalui Corporate University - Nadya Megawati Rachman; Ratnaningsih Hidayati (Cendekia Niaga, 2020)
As an organization's strategic tool for developing Human Resources competencies, the initiation of the formation of the Ministry of Trade Corporate University requires a blueprint. Therefore, the purpose of writing this paper is to create an initial thinking framework for the development of the Ministry of Trade's Corporate University. The analytical method used in this research is to study relevant scientific literature. The results of the study show that the Ministry of Trade's Corporate University Initiation should start with a paradigm shift about learning from all relevant stakeholders. The foundation of this paradigm shift is the existence of a good learning strategy and leadership with a change initiative initiated by the top leadership of the organization. There are five pillars of the Ministry of Trade, Corporate University, namely Integrated Career Path and Human Capital Development, Knowledge Management, Learning Innovation, Network and Partnership, and Backbone Infrastructure.